Political repercussions of the phenomenon of money laundering in Iraq After 2003 (قضايا سياسية, 2024)
Money Laundering Has Become One Of The Most Widespread, Secretive, And Organized Crimes Worldwide, Causing Concern For Officials In Combating Corruption In General. It Is Linked To Illicit Activities That Generate Significant Financial Returns, Leading To Direct Problems On Political, Economic, And Social Aspects. Money Laundering Undermines The State's Control Over Public Policy, Contributing To A Disruption Of The Balance And Stability Of The Country, Which Are Fundamental Pillars For Achieving Prosperity, Development, And Progress In Any Society. This Negatively Impacts The Public Interest Of The State Politically, As It Poses A Threat To Political Stability, Leading To The Spread Of Political Corruption Through The Use Of Money Laundering Within The Gove ,